Reliability and validity of six-minute step test in patients with heart failure - Marinho, Renan Shida (2021)
Exercise intolerance is the hallmark consequence of advanced chronic heart failure (HF). The six-minute step test (6MST) has been considered an option for the six-minute walk test because it is safe, inexpensive, and can be applied in small places. However, its reliability and concurrent validity has still not been investigated in participants with HF with reduced ejection fraction (HFrEF). Clinically stable HFrEF participants were included. Reliability and error measurement were calculated by comparing the first with the second 6MST result. Forty-eight hours after participants underwent the 6MST, they were invited to perform a cardiopulmonary exercise test (CPET) on a cycle ergometer. Concurrent validity was assessed by correlation between number of steps and peak oxygen uptake (V̇O2 peak) at CPET. Twenty-seven participants with HFrEF (60±8 years old and left ventricle ejection fraction of 41±6%) undertook a mean of 94±30 steps in the 6MST. Intra-rater reliability was excellent for 6MST (ICC=0.9), with mean error of 4.85 steps and superior and inferior limits of agreement of 30.6 and -20.9 steps, respectively. In addition, strong correlations between number of steps and CPET workload (r=0.76, P<0.01) and peak V̇O2 (r=0.71, P<0.01) were observed. From simple linear regression the following predictive equations were obtained with 6MST results: V̇O2 peak (mL/min) = 350.22 + (7.333 × number of steps), with R2=0.51, and peak workload (W) = 4.044 + (0.772 × number of steps), with R2=0.58. The 6MST was a reliable and valid tool to assess functional capacity in HFrEF participants and may moderately predict peak workload and oxygen uptake of a CPET.